Exercise Promotes Mirnas’ Change in Cardiac Fibrosis - Alaydrus, Nadia; Sylviana, Nova; Teesa, Putri (Journal La Medihealtico, 2024)
Cardiac fibrosis is a pathological feature as a key factor in cardiac remodelling, thus progressing to heart failure. MicroRNAs (miRNAs) are crucial intracellular mediators of various biological processes, involved in the regulation of physiological and pathological processes. Recently, it has been shown that miRNAs were found to play a role in exercise-induced cardioprotection. Studies in human and animal subject with variety of acute and chronic exercise were observed. This review highlights impacts of exercise on the miRNA levels associated with cardiac fibrosis.